The role of glucocorticoids in increasing cardiovascular risk - Deng, Hai-Wei; Mei, Wei-Yi; Xu, Qing; Zhai, Yuan-Sheng; Lin, Xiao-Xiong; Li, Jie; Li, Teng-Fei; Zheng, Qian; Chen, Jin-Sheng; Ou-Yang, Shun; Huang, Zhi-Bin; Cheng, Yun-Jiu (Frontiers in Cardiovascular Medicine, 2023)
Introduction Different studies provide conflicting evidence regarding the potential for glucocorticoids (GCs) to increase the risk of cardiovascular diseases. This study performed a systematic review and meta-analysis to determine the correlation between GCs and cardiovascular risk, including major adverse cardiovascular events (MACE), death from any cause, coronary heart disease (CHD), heart failure (HF), and stroke. Methods We performed a comprehensive search in PubMed and Embase (from inception to June 1, 2022). Studies that reported relative risk (RR) estimates with 95% confidence intervals (CIs) for the associations of interest were included. Results A total of 43 studies with 15,572,512 subjects were included. Patients taking GCs had a higher risk of MACE (RR = 1.27, 95% CI: 1.15–1.40), CHD (RR = 1.25, 95% CI: 1.11–1.41), and HF (RR = 1.92, 95% CI: 1.51–2.45). The MACE risk increased by 10% (95% CI: 6%–15%) for each additional gram of GCs cumulative dose or by 63% (95% CI: 46%–83%) for an additional 10 μg daily dose. The subgroup analysis suggested that not inhaled GCs and current GCs use were associated with increasing MACE risk. Similarly, GCs were linked to an increase in absolute MACE risk of 13.94 (95% CI: 10.29–17.58) cases per 1,000 person-years. Conclusions Administration of GCs is possibly related with increased risk for MACE, CHD, and HF but not increased all-cause death or stroke. Furthermore, it seems that the risk of MACE increased with increasing cumulative or daily dose of GCs.